Synthetic oleanane triterpenoids suppress MYB oncogene activity and sensitize T-cell acute lymphoblastic leukemia cells to chemotherapy - Tejera Nevado, Paloma; Tešan Tomić, Tajana; Atefyekta, Ali; Fehr, André; Stenman, Göran; Andersson, Mattias K. (Frontiers in Oncology, 2023)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematologic malignancy with poor prognosis. The MYB oncogene encodes a master transcription factor that is activated in the majority of human T-ALLs. In the present study, we have performed a large-scale screening with small-molecule drugs to find clinically useful inhibitors of MYB gene expression in T-ALL. We here identify several pharmacological agents that potentially could be used to treat MYB-driven malignancies. In particular, treatment with the synthetic oleanane triterpenoids (OTs) bardoxolone methyl and omaveloxolone decreased MYB gene activity and expression of MYB downstream target genes in T-ALL cells with constitutive MYB gene activation. Notably, treatment with bardoxolone methyl and omaveloxolone led to a dose-dependent reduction in cell viability and induction of apoptosis at low nanomolar concentrations. In contrast, normal bone marrow-derived cells were unaffected at these concentrations. Bardoxolone methyl and omaveloxolone treatment downregulated the expression of DNA repair genes and sensitized T-ALL cells to doxorubicin, a drug that is part of the standard therapy of T-ALL. OT treatment may thus potentiate DNA-damaging chemotherapy through attenuation of DNA repair. Taken together, our results indicate that synthetic OTs may be useful in the treatment of T-ALL and potentially also in other MYB-driven malignancies.